2019
DOI: 10.1002/hep.30485
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Specificity Phosphatase 26 Protects Against Nonalcoholic Fatty Liver Disease in Mice Through Transforming Growth Factor Beta–Activated Kinase 1 Suppression

Abstract: Nonalcoholic fatty liver disease (NAFLD), which has a wide global distribution, includes different stages ranging from simple steatosis to nonalcoholic steatohepatitis, advanced fibrosis, and liver cirrhosis according to the degree of severity. Chronic low‐grade inflammation, insulin resistance, and lipid accumulation are the leading causes of NAFLD. To date, no effective medicine for NAFLD has been approved by governmental agencies. Our study demonstrated that the expression of dual‐specificity phosphatase 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…4C) ( Fig. 3g) andaltered the expression of DUSP1 71 (Fig. 3g), in further support of the stress response induced by ethanol in the liver chip.…”
Section: Ethanol-induced Steatosis In the Liver-chipsupporting
confidence: 71%
“…4C) ( Fig. 3g) andaltered the expression of DUSP1 71 (Fig. 3g), in further support of the stress response induced by ethanol in the liver chip.…”
Section: Ethanol-induced Steatosis In the Liver-chipsupporting
confidence: 71%
“…A more recent study showed that DUSP12, which plays an important role in brown adipocyte differentiation, physically binds to ASK1, promotes its dephosphorylation, and inhibits its action on p38α/β in order to reducelipogenesis and to suppress lipid accumulation in livers of high-fat fed mice [167]. Similar to DUSP12, DUSP14, DUSP26 and MKP-5 suppress the development of hepatic steatosis by inhibiting p38s [167][168][169][170]. Both DUSP14 and DUSP26 directly bind and dephosphorylate TAK1 kinase, which results in the inhibition of TAK1 and its downstream targets JNKs and p38s [168,169].…”
Section: The Role Of P38s In the Livermentioning
confidence: 99%
“…Similar to DUSP12, DUSP14, DUSP26 and MKP-5 suppress the development of hepatic steatosis by inhibiting p38s [167][168][169][170]. Both DUSP14 and DUSP26 directly bind and dephosphorylate TAK1 kinase, which results in the inhibition of TAK1 and its downstream targets JNKs and p38s [168,169]. MKP-5 prevents the development of hepatic steatosis by suppressing p38-ATF2 and p38-PPARγ signaling axis to reduce hepatic lipid accumulation [170].…”
Section: The Role Of P38s In the Livermentioning
confidence: 99%
“…ASK1 is upregulated in NASH patients and correlates with the fibrosis stage. In animal models, inhibition of ASK1 as well as molecules upstream and downstream of the pathway improved NASH and hepatic lipid metabolism (36,37). Despite encouraging results from a small phase 2 study (38), selonsertib failed to improve NASH or fibrosis in the phase 3 STELLAR Study (https:// www.gilead.com/news-and-press/press-room/pressreleases/2019/4/gilead-announces-topline-data-fromphase-3-stellar3-study-of-selonsertib-in-bridging-fibrosis-f3-due-to-nonalcoholic-steatohepatitis-nash, accessed on 25 April 2019).…”
Section: Selonsertibmentioning
confidence: 99%